The fine ware supply of the earliest Roman units on the lower Danubian limes: the case of the First Cohort in Novae - Dyczek, Piotr (Rei Cretariae Romanae Fautorum Acta, 2022)
New excavations in Novae in 2011 were carried out in sector XII of the site located on the eastern side of the principia, expecting to find the barracks of the First Cohort. We have found the remains of an earth-and-timber structure belonged to a double wooden army barracks of VIII Augusta. The excavation revealed 29 pits connected with the two successive building phases revealed by stratigraphic analysis of the remains. The earliest set of pits can be placed around the middle of the 1st century AD, the years 45–49/50 AD. The second phase, associated with rebuilding, thus fell between about AD 50 and AD 69 – the arriving of I Italica. The most interesting finds from the pits are fragments of different types of terra sigillata. One may note, however, some common characteristics. Vessel types are not particularly sophisticated and neither is the decoration. The set is fairly simple and repetitive. But new forms of Italic and southern Gaul products reached both legions very early, directly after starting to be produced. Generally more than half of the vessels (54 %) came from Italic workshops; 31 % were from southern Gaul and 15 % were different Eastern Sigillata.